2016
DOI: 10.5553/tvc/0165182x2016058001003
|View full text |Cite
|
Sign up to set email alerts
|

Terug naar huis? Veranderingen in woonsituaties tijdens detentie en na vrijlating

Abstract: Hoewel een goede woonsituatie van ex-gedetineerden een van

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…This may indicate homelessness. Research on a sample of Dutch formerly incarcerated adults showed that 7% to 12% of the formerly incarcerated adults were homeless 1 to 6 months following release from prison (Wensveen et al, 2016). However, it is also possible that no address is known because subjects either forgot to register after moving to a new residence in the Netherlands, did not want to register at an address as this might affect the public assistance eligibility for another person registered at the address, or that subjects moved (temporarily) outside the Netherlands without providing this information to the municipality.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate homelessness. Research on a sample of Dutch formerly incarcerated adults showed that 7% to 12% of the formerly incarcerated adults were homeless 1 to 6 months following release from prison (Wensveen et al, 2016). However, it is also possible that no address is known because subjects either forgot to register after moving to a new residence in the Netherlands, did not want to register at an address as this might affect the public assistance eligibility for another person registered at the address, or that subjects moved (temporarily) outside the Netherlands without providing this information to the municipality.…”
Section: Discussionmentioning
confidence: 99%
“…Uiteraard kan het ook zo zijn dat deze gedetineerden geen zorgvragen hebben en daarom geen behoefte hebben aan contact. Maar omdat ook tijdens het detentietraject hulpvragen kunnen ontstaan op de leefgebieden (Dirkzwager et al, 2018;Noordhuizen & Weijters, 2012;Wensveen et al, 2016), is het mogelijk toch van belang ook bij langer gestraften tussentijds te peilen of alle leefgebieden nog op orde zijn. Dit hoeft voor de langer gestraften wellicht niet wekelijks, maar kan bijvoorbeeld om de drie maanden plaatsvinden in de vorm van een kort contactmoment.…”
Section: Aanbevelingen Voor Intern Contactunclassified
“…Na detentie kampt maar liefst 58% van de ex-gedetineerden met schulden en ongeveer 77% genereert na vrijlating geen inkomen uit arbeid (Beerthuizen et al, 2015). Daarnaast heeft 33% na vrijlating geen eigen huur-of koopwoning (Wensveen et al, 2016) en lijdt 34% onder een vorm van verslaving (Den Bak et al, 2018). Deze problemen bemoeilijken een succesvolle re-integratie en vergroten de kans op recidive (Graffam et al, 2004;Hoeve et al, 2014;Ramakers et al, 2017).…”
Section: Introductieunclassified
See 1 more Smart Citation
“…Upon release, more than 70% of Dutch prisoners are unemployed and more than half encounter financial difficulties ( Beerthuizen et al, 2015 ; Ramakers, 2014 ). Moreover, one third of Dutch prisoners find themselves in unstable housing situations or experience drug related problems ( Den Bak et al, 2018 ; Wensveen et al, 2016 ) and 15% do not possess valid identification ( Weijters et al, 2018 ). Similar problems are reported worldwide (e.g., Abbott et al., 2016 ; McSweeney & Hough, 2006 ; Visher et al, 2004 ).…”
mentioning
confidence: 99%